Genetic counselling for pulmonary arterial hypertension: a matter of variable variability - Leter, E. M. (Bohn Stafleu van Loghum, 2011)
We report three cases which highlight the complex considerations surrounding genetic counselling for pulmonary arterial hypertension (PAH). The first counselee developed PAH symptoms shortly after his daughter’s death from PAH and was diagnosed with a delay of 1 year. An early diagnosis of familial PAH was established in the second counselee. Oral therapy was initiated immediately, and her functional status has since remained stable. The third counselee was a healthy woman who struggled to cope with her risk for familial PAH, having lost two siblings from the disease. These cases show that incomplete penetrance and variable expression need particular attention during clinical assessment and genetic counselling of heritable PAH patients and family members.